Pengembangan Wirausaha Di Science And Technology Park (STP) Untuk Meningkatkan Daya Saing Dan Pemasaran Kopi Produksi Kabupaten Kaur, Bengkulu - Djatmiko Pinardi; Daru Mulyono (Jurnal Kebijakan Pembangunan, 2017)
Bengkulu includes the top five of Indonesian coffee producers and is well known as the " robusta gold triangle" province besides Lampung and South Sumatra. Total area of coffee plantations in Kaur is currently recorded at 6,978 ha, all of which are community coffee managed using traditional technology. Therefore, until now the marketing of Kaur coffee still not well developed. This study aims to foster coffee entrepreneurs so as to produce beginners coffee entrepreneurs based on technology in Micro, Small and Medium Enterprises (MSMEs) through the of Science and Technology Park (STP). This study is a descriptive analytic study using primary data of Kaur coffee bean taste analysis in Centre for Coffee and Cocoa Research, Jember. Whereas secondary data collected through searches from various scientific publications and plantation statistics of Kaur Regency, Bengkulu. The result of the study shows that the quality of coffee from Kaur Regency is very good and some are excellent. Therefore, the development of coffee entrepreneur through incubation in STP Pondok Pusaka, Kabupaten Kaur is a very strategic policy. Through the development of this entrepreneurship by applying more advanced technology is expected to create a new entrepreneurship that is able to improve the competitiveness of Kaur coffee. Increasing the competitiveness of coffee is expected to penetrate into national and global markets so that it can become the motor of local economic movers and lift the welfare of local communities significantly. Abstrak Bengkulu termasuk lima besar produsen kopi Indonesia dan terkenal sebagai provinsi “segitiga emasrobusta” selain Lampung dan Sumatera Selatan. Luas areal perkebunan kopi di Kaur saat ini tercatat sebesar6.978 ha yang semuanya merupakan kopi rakyat yang dikelola dengan menggunakan teknologitradisional.Oleh karena itu sampai saat ini pemasaran kopi Kaur masih belum berkembang dengan baik.Kajian ini bertujuan untuk membina wirausaha kopi sehingga dihasilkan wirausaha kopi pemula berbasisteknologi pada skala Usaha Mikro, Kecil, dan Menengah (UMKM) melalui wadah Science and TechnologyPark (STP). Kajian ini merupakan kajian deskriptif analitik dengan menggunakan data primer hasil uji citarasa biji kopi produksi Kaur di Pusat Penelitian Kopi dan Kakao, Jember. Sedangkan data sekunder yangdikumpulkan melalui penelusuran dari berbagai publikasi ilmiah maupun statistik perkebunan KabupatenKaur, Bengkulu. Hasil kajian menunjukkan bahwa kualitas kopi dari Kabupaten Kaur tergolong Sangat Baikbahkan ada yang tergolong Excellent. Oleh karena itu pengembangan wirausaha kopi melalui inkubasi di STPPondok Pusaka, Kabupaten Kaur ini merupakan kebijakan yang sangat strategis. Melalui pengembanganwirausaha ini dengan menerapkan teknologi yang lebih maju diharapkan akan memunculkan wirausaha baruyang tangguh yang mampu meningkatkan daya saing kopi Kaur. Meningkatnya daya saing kopi inidiharapkan bisa menembus ke pasar nasional maupun global sehingga mampu menjadi motor penggerakperekonomian daerah dan mengangkat kesejahteraan masyarakat daerah secara nyata.